2010
DOI: 10.1002/zaac.200900588
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 1,1′‐Diphosphaferrocene with CuCl and CuBr Resulting in Cu4P4X4Fe2 (X = Cl, Br) Complexes with Adamantane‐like Topologies 

Abstract: Cu 4 P 4 X 4 Fe 2 (X = Cl, Br) cages are formed upon reactions of octaethyl-1,1'-diphosphaferrocene (odpf) with the respective Cu I halide in CH 2 Cl 2 /CH 3 CN solvent mixtures. These cages have adamantoid Cu 4 X 4 P 2 cores with two planar anelated CuP 2 Fe rings as the flaps. Both complexes 1 and 2 feature tri-and tetracoordinate Cu I ions and an additional acetonitrile solvent molecule in the crystal. In 1, the solvent molecule is coordinated to one copper ion whereas it remains uncoor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Thus 4 exhibits Cu I ions both in tricoordinate [Cu(1) and Cu(3)] and tetracoordinate [Cu(2) and Cu(4)] mode with distorted trigonal planar and tetrahedral coordination, respectively. As expected, the Cu–S and Cu–Br bond lengths of the tricoordinate copper ions are distinctly shorter than those of the tetracoordinate ones 36. For instance in 4a , the bond lengths of Cu(1) and Cu(3) with respective bridging atoms S(1), S(3), Br(2), or Br(4) (if available) are shorter than those involving Cu(2) and Cu(4) atoms.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Thus 4 exhibits Cu I ions both in tricoordinate [Cu(1) and Cu(3)] and tetracoordinate [Cu(2) and Cu(4)] mode with distorted trigonal planar and tetrahedral coordination, respectively. As expected, the Cu–S and Cu–Br bond lengths of the tricoordinate copper ions are distinctly shorter than those of the tetracoordinate ones 36. For instance in 4a , the bond lengths of Cu(1) and Cu(3) with respective bridging atoms S(1), S(3), Br(2), or Br(4) (if available) are shorter than those involving Cu(2) and Cu(4) atoms.…”
Section: Resultssupporting
confidence: 82%
“…It has been shown that reactions between copper(I) halides and thiourea or its derivatives frequently generate a variety of complexes, which have unpredictable stoichiometry and stereochemistry 37. This structural diversity originates from the propensity of the halide to act as terminal or bridging ligand and of the thiourea ligand to coordinate in a monodentate or a bridging mode 36. In the known tetranuclear Cu I systems with sulfur donor, the adamantanoid cages often contain the Cu 4 S 6 core,38 in which simply the soft anions like halides have the chance to bind with the copper site in a terminal fashion (Cl,39 I13,37).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations